Sirtuin 1 Inhibiting Thiocyanates (S1th)—A New Class of Isotype Selective Inhibitors of NAD+ Dependent Lysine Deacetylases - Wössner, Nathalie; Alhalabi, Zayan; González, Jessica; Swyter, Sören; Gan, Jin; Schmidtkunz, Karin; Zhang, Lin; Vaquero, Alejandro; Ovaa, Huib; Einsle, Oliver; Sippl, Wolfgang; Jung, Manfred (Frontiers in Oncology, 2020)
Sirtuin 1 (Sirt1) is a NAD+ dependent lysine deacetylase associated with the pathogenesis of various diseases including cancer. In many cancer types Sirt1 expression is increased. Higher levels have been associated with metastasis and poor prognosis. However, tumor suppressing properties of Sirt1 have also been observed and in some instances even a dual role for the same cancer type has been reported. Increased Sirt1 activity has been linked to life span extension of cells respectively organisms by promoting DNA repair processes and downregulation of tumor suppressor proteins. This may have the downside of enhancing tumor growth and metastasis. In mice embryonic fibroblasts depletion of Sirt1 was shown to decrease levels of DNA damage sensor histone H2AX. Impairment of DNA repair mechanisms can promote tumorigenesis but also lower chemoresistance towards DNA targeting therapies. Despite many biological studies, there is currently just one small molecule Sirt1 inhibitor in clinical trials. Selisistat (EX-527) reached phase III clinical trials for treatment of Huntington’s Disease. New small molecule Sirt1 modulators are crucial for investigation of the contradicting roles of Sirt1 in cancer. We tested a small library of commercially available compounds proposed by virtual screening against Sirt1, 2 and 3. A thienopyrimidone featuring a phenyl thiocyanate moiety was found to selectively inhibit Sirt1 with an IC50 of 13 μM. Structural analogues lacking the thiocyanate function did not show inhibition of Sirt1 revealing this group as key for selectivity and affinity towards Sirt1. Further analogues with higher solubility were identified through iterative docking studies and in vitro testing. The most active compounds (down to 5 µM IC50) were further studied in cells. The ratio of phosphorylated γH2AX to unmodified H2AX is lower when Sirt1 is depleted or inhibited. Our new Sirtuin 1 inhibiting thiocyanates (S1th) lead to similarly lowered γH2AX/H2AX ratios in mouse embryonic fibroblasts as Sirt1 knockout and treatment with the reference inhibitor EX-527. Additionally we were able to show inhibition of proliferation, migration and colony forming and hyperacetylation of Sirt1 targets p53 and H3 by S1th in cervical cancer cells (HeLa). These results reveal thiocyanates as a promising new class of selective Sirt1 inhibitors.